Best offer wins : a novel - Kashino, Marisa (Good morning America book club., 2025)
"An insanely competitive housing market. A buyer pushed to the breaking point. How far would you go for the American Dream? Eighteen months and eleven lost bidding wars into house-hunting in the overheated Washington, DC, suburbs, thirty-seven-year-old publicist Margo Miyake gets a tip about the perfect house, in the perfect neighborhood, slated to come up for sale in one month. Desperate to escape the cramped apartment she shares with her husband Ian-and, in turn, fix their marriage, have a baby, and get their life started-Margo becomes obsessed with buying the house before it's publicly listed and the masses descend with all-cash offers in hand. With some (harmless!) stalking and a bit of (very light!) trespassing, she worms her way into the homeowners' lives. But just when she believes she's won them over, they uncover her scheme and shut her out. Undeterred, Margo will prove again and again that there's nothing she won't try-no secret too dark to leverage, no tactic too unhinged-to finally kickstart the dream life she's worked so hard to achieve. A deeply dark, laugh-out-loud commentary on class, ambition, and the housing crisis, Best Offer Wins is a propulsive debut from a totally original voice-with a violent scream of female rage at its core"-- Provided by publisher.